2020
DOI: 10.1253/circj.cj-19-0936
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Late Gadolinium Enhancement Predicts Thromboembolic Events in Patients With Hypertrophic Cardiomyopathy

Abstract: Background: Thromboembolic complications such as ischemic stroke or peripheral arterial thromboembolism are known complications in hypertrophic cardiomyopathy (HCM). We sought to assess the clinical and cardiovascular magnetic resonance (CMR) characteristics of patients with HCM suffering from thromboembolic events and analyzed the predictors of these unfavorable outcomes. Methods and Results: The 115 HCM patients underwent late gadolinium enhanced (LGE) CMR and were included in the study. Follow-up was 5.6±3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(32 reference statements)
0
5
0
1
Order By: Relevance
“…Further to left atrial size and function, a recent study using cardiac magnetic resonance imaging demonstrated that HCM patients with paroxysmal AF have a greater extent of left atrial wall fibrosis on late gadolinium enhancement, together with a number of other functional and morphological features. 36 This association between AF and left atrial late gadolinium enhancement indicates the importance of assessing not only LV fibrosis, 37 but also left atrial fibrosis as an important adverse marker in HCM patients. In this context, the recently proposed concept of atrial failure 38 may also be relevant to the HCM population, because the presence of atrial failure may predispose a patient to new-onset AF.…”
Section: Discussionmentioning
confidence: 99%
“…Further to left atrial size and function, a recent study using cardiac magnetic resonance imaging demonstrated that HCM patients with paroxysmal AF have a greater extent of left atrial wall fibrosis on late gadolinium enhancement, together with a number of other functional and morphological features. 36 This association between AF and left atrial late gadolinium enhancement indicates the importance of assessing not only LV fibrosis, 37 but also left atrial fibrosis as an important adverse marker in HCM patients. In this context, the recently proposed concept of atrial failure 38 may also be relevant to the HCM population, because the presence of atrial failure may predispose a patient to new-onset AF.…”
Section: Discussionmentioning
confidence: 99%
“…CMR LGE extent (> 14.4%) has been found to be an independent predictor for thromboembolic complications in patients with HCM [56].…”
Section: Cardiomyopathiesmentioning
confidence: 97%
“…2022;12 (4) Utilidad de la resonancia magnética cardíaca Artículo de revisión que tienen más del 15% de fibrosis miocárdica dos veces mayor el riesgo de desarrollar muerte cardíaca súbita. (29,30) Adicionalmente el T1 mapping se encuentra incrementado al igual que el volumen extracelular (31,32) incluso en áreas donde no se observe hipertrofia (genotipo positivo, fenotipo negativo). (33,34) (Figura 3)…”
Section: Cardiomiopatía Hipertróficaunclassified